Temporomandibular Joint Diseases: Diagnosis and Management - Almeida, Luis Eduardo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Temporomandibular Joint Diseases are common and dificult to treat. From diagnosis to treatment, our options are in a broad range. Keeping updated with new technologies is extremely important for researchers and health professionals.